2021
DOI: 10.1111/ajad.13207
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of telehealth services for outpatient treatment of substance use disorders during the COVID‐19 pandemic

Abstract: Background and Objectives: The rapid scale-up of telehealth services for substance use disorders (SUDs) during the COVID-19 pandemic presented a unique opportunity to investigate patient experiences with telehealth. This study examined patient perceptions of telehealth in an outpatient SUD treatment program offering individual therapy, group therapy, and medication management. Methods: Two hundred and seventy adults receiving SUD outpatient treatment were eligible to complete a 23-item online survey distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 20 publications
6
34
0
Order By: Relevance
“…Furthermore, the restrictions seemed to cause dissatisfaction regarding remote group meetings. This observation is in line with Sugarman’s and colleagues’ [ 38 ] research, where they found that individuals experiencing SUD were not as satisfied with remote group therapy instead of remote individual therapy, because they were not able to connect as well with other participants as they were in face-to-face meetings. In our study we found that, according to the clients’ experiences, remote connections made interaction more premeditated, which eliminated the elements of spontaneity, naturalness, and interactivity.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the restrictions seemed to cause dissatisfaction regarding remote group meetings. This observation is in line with Sugarman’s and colleagues’ [ 38 ] research, where they found that individuals experiencing SUD were not as satisfied with remote group therapy instead of remote individual therapy, because they were not able to connect as well with other participants as they were in face-to-face meetings. In our study we found that, according to the clients’ experiences, remote connections made interaction more premeditated, which eliminated the elements of spontaneity, naturalness, and interactivity.…”
Section: Discussionsupporting
confidence: 88%
“…The benefits and concerns expressed were similar to those reported by clinicians in the US who transitioned to telehealth during COVID-19 ( Uscher-Pines et al, 2020 ). Similar to previous studies, participants also highlighted challenges in relation to lack of access to smartphones and phone charging facilities, limited broadband, language barriers and lack of privacy in the person's home or, for those who are homeless, no private location during remote consultation ( Lin et al, 2019 ; Sugarman et al, 2021 ; Tofighi et al, 2022 ; Uscher-Pines et al, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…However, this was conditional on any remote health assessments being followed-up with a face-to-face consultation within two to four weeks. The various considerations expressed by participants in relation to the development of these statements, reflected current literature regarding the potential benefits and challenges associated with increased access to telehealth ( Hser et al, 2021 ; Krawczyk, Fawole, et al, 2021 ; Sugarman et al, 2021 ; Uscher-Pines et al, 2020 ). For example, participants acknowledged that offering patients a remote health assessment, allows for increased access to care and minimises travel requirements, particularly for those living in rural locations.…”
Section: Discussionmentioning
confidence: 99%
“…Early applications have shown promise as a means of preventing premature dropout from SUD treatment [ 8 ]. The pandemic rapidly accelerated the implementation of telehealth services for mental health and substance use treatment [ 9 ], and both providers and participants have viewed these types of services favorably [ 10 , 11 ]. Unfortunately, little is known about the actual efficacy or effectiveness of individual SUD treatment in telehealth treatment settings [ 12 - 14 ], and even less about traditional group treatment formats [ 15 ].…”
Section: Introductionmentioning
confidence: 99%